2013
DOI: 10.1074/jbc.m113.476556
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone Receptor A Stability Is Mediated by Glycogen Synthase Kinase-3β in the Brca1-deficient Mammary Gland

Abstract: Background: Stabilization of progesterone receptors contributes to mammary tumorigenesis in Brca1-deficient mice. Results: Deficiency in phosphorylation on serine 390 of progesterone receptor A by GSK-3␤ enhances the receptor stability. Conclusion: Stabilization of progesterone receptor A is mediated by GSK-3␤ kinase in the Brca1-deficient mammary gland. Significance: This finding provides a novel insight of how tumor suppression of Brca1 is mediated by PR-A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…PR phosphorylation provokes its polyubiquitination, marking the receptor to be degraded by the 26S proteasome (15,18,20,43). Lange et al reported that degradation of PR induced by the progestin R5020 occurs within 4 to 12 hours after treatment in breast cancer cells (15).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…PR phosphorylation provokes its polyubiquitination, marking the receptor to be degraded by the 26S proteasome (15,18,20,43). Lange et al reported that degradation of PR induced by the progestin R5020 occurs within 4 to 12 hours after treatment in breast cancer cells (15).…”
Section: Discussionmentioning
confidence: 98%
“…It has been reported that four kinases are able to phosphorylate PR. Residue Ser81 can be phosphorylated by casein kinase II (CKII) (17), residues Ser25, Ser190, Ser213, Ser294, Ser554, Ser676 can be phosphorylated by cyclin-dependent kinase 2 (CDK2) (14,16), Ser162 and Ser294 by mitogen activated protein kinases 44 and 42 (MAPK 44/42) (15), and recently, it has been reported that Ser390 is phosphorylated by glycogen synthase kinase-3␤ (GSK3␤) (18). MAPKs are able to phosphorylate PR, increase its transcriptional activity and promote its degradation by the 26S proteasome (20).…”
mentioning
confidence: 99%
“…Other receptors reported to be phosphorylated by GSK3 include the androgen receptor, which reduces its activation of transcription (Salas et al, 2004; Wang et al, 2004), the prolactin receptor, which targets it for proteasomal degradation (Plotnikov et al, 2008), the progesterone receptor, which regulates its stability (Wang et al, 2013b), LRP6, which promotes the recruitment of Axin to LRP6 (Zeng et al, 2005), and the IGF-1 receptor, which regulates its signaling and trafficking (Nemoto et al, 2010; Kelly et al, 2012). …”
Section: Gsk3 Interactions With Receptors and Receptor-coupled Sigmentioning
confidence: 99%
“…Afterwards cells were washed three times in PBS for 3 min. Cells were then incubated at 37°C overnight (no CO 2 ) with fresh SA-β-gal staining solution at pH 6.0: 1 mg of 5-bromo-4-chloro-3-indolyl β-D galactosidase (X-Gal) per ml (stock solution = 20 mg of potassium ferrocyanide/5 mM potassium ferricyanide/150 mM NaCl/2 mM MgCl2) [32]. Cells were washed twice and observed under an ordinary light microscopy.…”
Section: Methodsmentioning
confidence: 99%